Analisis Sistem Aplikasi Customer Relationship Management Dengan Metode Waterfall Untuk Mempertahankan Loyalitas Dan Kepuasan Pelanggan Pada PT Network Lintas Fiberindo - Debi Numansah; Ines Heidiani Ikasari (CV. Multi Kreasi Media, 2023)
Customer satisfaction and loyalty are to be noticed by PT Network Lintas Fiberindo where the company is engaged in internet services. The company innovates by utilizing modern technology on the system so that customers do not switch to other internet service companies and achieve better service. CRM (Customer Relationship Management) is a system that can help companies improve customer service using the internet more effectively and efficiently. Customers can provide ratings & reviews, complaints, and suggestions with this system. Its design uses the waterfall method. This research produces an application that helps customers to provide input to the company regarding the company's service quality.